Lesbian, gay, bisexual, and transgender clinical competence of health professionals in Poland and Spain: results of the health exclusion research in Europe (HERE) study - Piotr Karniej; Anthony Dissen; Łukasz Pietrzykowski; Raúl Juárez-Vela; Antonio Martinez Sabater; Janina Kulińska; Jakub Zieliński; Michał Czapla (BMC Medical Education)
Abstract Introduction Health disparities experienced by lesbian, gay, bisexual, and transgender (LGBT) individuals have been partially attributed to healthcare professionals’ lack of cultural competence in addressing their specific needs. This study aimed to assess the differences in competencies and preparedness among health professionals from Poland and Spain when working with LGBT patients. Methodology Data were collected between June and August 2024 through a cross-sectional survey involving 673 health professionals (Mage = 33.54, SD = 9.74; 61.5% female), including 273 participants from Spain and 400 from Poland. Participants completed a self-administered survey, which included sociodemographic questions and the Lesbian, Gay, Bisexual, and Transgender Development of Clinical Skills Scale (LGBT-DOCSS). Multivariate linear regression was used to analyze predictors of clinical preparedness, attitudes, and knowledge regarding LGBT care. Clinical trial number: not applicable. Results Spanish health professionals showed higher total LGBT-DOCSS scores compared to Polish participants (B = 0.503, p < 0.001). Gender was a significant predictor, with men scoring higher in clinical preparedness (B = 0.771, p = 0.002), while women scored higher in attitudes (B = -0.457, p < 0.001). In Poland, age was positively correlated with clinical preparedness (B = 0.034, p = 0.022), and physicians scored significantly higher in overall competency compared to nurses/midwives (B = 0.621, p = 0.005). Participation in LGBT-related training was associated with higher clinical preparedness in both countries, with those attending training 3 or more times scoring higher than those who never attended (B = 1.659, p < 0.001). Conclusion The study revealed significant differences in LGBT competency between Polish and Spanish health professionals. Factors such as gender, age, profession, and participation in LGBT-related training were associated with these competencies. Results suggest that a more tailored approach in professional education and training may be necessary to ensure all health workers possess adequate skills and attitudes toward LGBT care.